Character Strategies – Supporting Characters in the Movie "Easy A" to Release Feelings of Inferiority - Setianti Nur Mahatmi; Sukarjo Waluyo; M. Suryadi (Jurnal Sastra Indonesia, 2024)
Lack of self-confidence often occurs in every individual. In general, every individual experiences this experience in living his life. Ostracism is an event that is often encountered in the phenomenon of human life. To be free from this experience, every individual often tries to free himself from feelings of inferiority or distrust. In the film "Easy A," there are three supporting characters named Evan, Bryan, and Eric Ling who experience self-doubt and are ostracized by their school friends because the three characters are considered to have personalities that do not conform to expected social norms in that environment. Therefore, Evan, Bryan, and Eric Ling tried to escape their self-doubt and become individuals in line with what their school friends had set them up for. To get out of their feeling of inferiority, they used the level of popularity of the main character in the film, Olive Pendhergast, who was famous because of false rumors that she was no longer a virgin and dated many men who were deliberately spread by herself to make herself famous. The method used is a literary psychology approach using theories from David Brodwell's film elements and Adler's theory. This research was carried out to understand how an individual's efforts can free themselves from feelings of inferiority in social life through the perspective of the three supporting characters of the film "Easy A." The author found that the three supporting characters of the film "Easy A" have four ways to let go of feelings of inferiority to Adler's theory: making excessive efforts, being hasty or impatient, having solid impulses, and not considering other people.